Wound formation, wound size, and progression of wound healing after intratumoral treatment of mast cell tumors in dogs with tigilanol tiglate. (12th January 2021) - Reddell, Paul; De Ridder, Thomas R.; Morton, John M.; Jones, Pamela D.; Campbell, Justine E.; Brown, Graham; Johannes, Chad M.; Schmidt, Peter F.; Gordon, Victoria
Abstract: Background: Tigilanol tiglate (TT) is a novel small molecule for intratumoral treatment of nonmetastatic mast cell tumors (MCTs) in dogs. In a randomized controlled clinical study, 75% of dogs that received a single TT treatment achieved complete resolution of the MCT by 28 days, with no recurrence in 93% of dogs at 84 days. Critical to TT's efficacy was the area of the wound (tissue deficit) after slough of the necrotic tumor relative to pretreatment tumor volume. Objectives: To analyze data collected during the previous study to (a) describe wounds after slough of treated MCTs and (b) identify determinants of wound area and speed of wound healing. Methods: Wound presence, condition, and area were determined from clinical records of 117 dogs over 84 days after a single intratumoral TT treatment. Results: Tumor slough occurred 3 to 14 days after treatment, exposing granulation tissue in the wound bed. Wound area after tumor slough in general was related to pretreatment tumor volume, with maximal recorded wound area fully evident in 89% of dogs by day 7. In dogs achieving complete tumor resolution, all wounds were left to heal by secondary intention. Bandaging and other wound management interventions only were required in 5 dogs. Time to healing (ie, full re‐epithelialization of treatment site) depended on wound area and location on the body, with most wounds being fully healed between 28 and 42 days after treatment. Conclusions: Wound area and healing after slough of TT‐treated tumors follow a consistent clinical pattern for most dogs.